Rehabilitees’ conceptions of participation after a six-month rehabilitation period: a phenomeno-graphic study - Alanko, Tuulikki; Kröger, Teppo; Nikander, Riku; Piirainen, Arja; Vuoskoski, Pirjo (Physiotherapy theory and practice, 2024)
A prerequisite for successful rehabilitation is that the rehabilitees are in central role of the rehabilitation process. However, the rehabilitees and rehabilitation professionals may both lack knowledge and understanding of how to implement rehabilitee-centered participation in practice. This study aimed to explore the qualitatively different ways of understanding rehabilitee participation as conceptualized by the rehabilitees. We generated data from individual interviews with 20 rehabilitees after a six-month rehabilitation process. These interviews were analyzed based on phenomenographic methodology. We identified three understandings of rehabilitee participation as conceptualized by the participants: 1) Dependent participation; 2) Progressive participation; and 3) Committed participation. These categories varied according to four themes: 1) Rehabilitation process; 2) Rehabilitation in everyday life; 3) Interaction in rehabilitation; and 4) Rehabilitation support network. We also identified critical aspects highlighting differences between the qualitatively distinct categories. This study generated new insights into understanding the phenomenon of rehabilitee participation, as conceptualized by rehabilitees themselves. The findings in terms of three descriptive categories and critical aspects between the categories, reflect the ascending and shifting complexity from dependent to progressive and committed participation. These findings as such can be utilized in the design, development, and implementation of rehabilitee participation and rehabilitee-centered practice.